(untitled) (Raparin Journal of Humanities (RJH), 2023)
This study aims to analyze and compare three computer curriculum Text books, which are the information technology book for the seventh grade in the Kurdistan region, the computer book for the first intermediate grade in Iraq, and the computer book for the seventh grade in Jordan, in order to know which fields in the books have the greatest space and importance, and the areas that It has the least space and importance. To achieve the objectives of this research, all the topics in the three books have been analyzed. The research community consists of three books (Information Technology/Kurdistan Region, Computer/Iraq, and Computer/Jordan). To implement the objectives of the research and collect information, the classification form was used as a research tool consisting of 175 sections, and after the issuance of the validity and reliability of the research tool, this form was divided into 100 experts in the field of computer in universities and governmental and non-governmental institutes in the Kurdistan Region, as well as education teachers in basic public schools. After taking the opinions of experts, analyzing them and emptying the research tools, statistical formulas were used, such as (percentage, arithmetic mean), the most important results of the study were presented.